Improving Students’ Vocabulary Mastery Through Think-Pair- Share with Picture Word Inductive Model (PWIM) - Simon, Maria Kristina (Universitas Galuh, 2025)
This study aims to improve the English vocabulary mastery of seventh-grade students at SMPK Sang Timur Malang through the implementation of the Think-Pair-Share (TPS) and Picture Word Inductive Model (PWIM) teaching methods. The research was conducted as a classroom action research (CAR) carried out in one cycle consisting of four meetings. Each stage of the research included planning, action, observation, and reflection. Data were collected through observations, tests, reflective journals, questionnaires, and interviews. The findings showed that the combination of TPS and PWIM effectively improved students’ vocabulary mastery. This was evident from the improvement in test scores, improved student engagement during the learning process, and positive responses toward the methods used. Therefore, this teaching strategy proves to be effective and applicable for supporting vocabulary learning in junior high school English classes.